The Gonium pectorale genome demonstrates co-option of cell cycle regulation during the evolution of multicellularity - Erik R. Hanschen; Tara N. Marriage; Patrick J. Ferris; Takashi Hamaji; Atsushi Toyoda; Asao Fujiyama; Rafik Neme; Hideki Noguchi; Yohei Minakuchi; Masahiro Suzuki; Hiroko Kawai-Toyooka; David R. Smith; et al. (Nature Communications, 2016)
The undifferentiated Gonium pectorale represents the initial transition to multicellularity. Here, Bradley Olson, Erik Hanschen and colleagues describe the genome of Gonium pectorale, demonstrating that co-option of the retinoblastoma cell cycle regulatory pathway was a key genetic change in the evolution of multicellularity.